Toxicity of Various Pyrolysis Liquids From Biosolids on Methane Production Yield - Seyedi, Saba; Venkiteshwaran, Kaushik; Zitomer, Daniel (Frontiers in Energy Research, 2019)
Aqueous pyrolysis liquid (APL) is a high-COD byproduct of wastewater biosolids pyrolysis that is comprised of numerous complex organic compounds and ammonia nitrogen (NH3-N). One potential beneficial use of APL is as a co-digestate to produce more biogas in anaerobic digesters. However, some APL organics and NH3-N are known to inhibit methane-producing microbes. Autocatalytic pyrolysis which uses previously-produced biochar as a catalyst during biosolids pyrolysis, increases energy-rich py-gas while eliminating bio-oil production and reducing COD concentration in the APL (catalyzed APL). However, the catalyzed APL still has a high organic strength and no suitable treatment strategies have yet been identified. In this study, the methane production yields and methanogenic toxicity of non-catalyzed and catalyzed APLs were investigated. Both non-catalyzed and catalyzed APLs were produced at 800°C from a mix of digested primary and raw waste activated sludge from a municipal water resource reclamation facility. Using the anaerobic toxicity assay, APL digester loading rates higher than 0.5 gCOD/L for non-catalyzed and 0.10 gCOD/L for catalyzed APL were not sustainable due to toxicity. The IC50 values (APL concentration that inhibited methane production rate by 50%) for non-catalyzed and catalyzed APLs were 2.3 and 0.3 gCOD/L, respectively. Despite having significantly fewer identified organic compounds catalytic APL resulted in higher methanogenic toxicity than non-catalytic APL. NH3-N was not the main inhibitory constituent and other organics in APL, including 3,5-dimethoxy-4-hydroxybenzaldehyde, 2,5-dimethoxybenzyl alcohol, benzene, cresol, ethylbenzene, phenols, styrene, and xylenes as well as nitrogenated organics (e.g., benzonitrile, pyridine) ostensibly caused considerable methane production inhibition. Future research focused on pretreatment methods to overcome APL toxicity and the use of acclimated biomass to increase methane production rates during APL anaerobic digestion or co-digestion is warranted.